2005
DOI: 10.1097/01.aids.0000191487.69414.88
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and survival of AIDS patients with hepatitis C: the Brazilian National Cohort of 1995–1996

Abstract: Brazilian AIDS patients with hepatitis C have a shorter survival than those without, but this seems to be mainly as a result of their receiving less antiretroviral treatment. We cannot say whether this is because of the fear of hepatotoxicity, an inability to tolerate treatment, or for other reasons. To improve survival, these patients need optimal treatment of their HIV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…6,8 The needles and syringes were bought the majority of the time (89%). The trash was the location for throwing away used syringes and needles, mentioned by 63%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 The needles and syringes were bought the majority of the time (89%). The trash was the location for throwing away used syringes and needles, mentioned by 63%.…”
Section: Discussionmentioning
confidence: 99%
“…2, ** A cohort study conducted among AIDS cases diagnosed from 1995 on, found a prevalence rate of 33% for hepatitis C. 6 Another study among IDUs in Santos found high prevalence rates of hepatitis C among IDUs: 84.8% and 20.9% among non IDUs. This indicates that exposure to blood and sexual relations with IDUs are the main risk factors for HCV transmission among HIV positive patients.…”
Section: Introductionmentioning
confidence: 98%
“…In a large retrospective study of 833 AIDS patients, 33% were reportedly seropositive for hepatitis C virus [21]. These patients had a higher mortality although this was thought to be multifactorial.…”
Section: Co-infection With Other Oncogenic Virusesmentioning
confidence: 99%
“…During these years, comprehensive response to HIV took place, and after the introduction of highly active antiretroviral therapy (HAART), hepatitis C has also been understood as a risk factor for mortality among people living with HIV/AIDS (PLWHA). 18,19 Considering the importance of viral hepatitis and the demand of structure for prevention and control of this disease at every level of health care, 20,21 We report 12 years of Brazil's experience in confronting hepatitis C infection and its consequences through a public health approach, with universal access as the baseline.…”
Section: Introductionmentioning
confidence: 99%